KOMBINASI GEOLISTRIK DAN GRID SAMPLING UNTUK MENGIDENTIFIKASI ADANYA KONTAMINASI HYDROCARBON PADA TANAH - Supriyadi Supriyadi (SIMETRIS, 2020)
Hydrocarbon at ground level can be seen visually but this cannot produce accurate quantitative and qualitative values ​​in determining the total volume of the contaminated soil. Therefore a study is needed that can explain quantitatively and qualitatively on contaminated soil so as to facilitate handling and management. Geoelectricity is a quantitative method that can be used in determining soil surface conditions. Qualitatively, the composition of the soil can be proven by laboratory sampling to determine whether it is included in the category of hazardous and toxic waste (LB3) or not in accordance with Annex V contained in Government Regulation No.101 of 2014. This study focuses on the stages to identify their existence. hydrocarbon in the soil using a combination of geoelectric and grid sampling so as to get a more accurate volume of the indicated soil contamination. Whereas the limitation of this study is that it is carried out at a former B-mediation facility that is suspected of being contaminated. Based on the geoelectric studies that have been carried out, the volume of the soil surface that is suspected to be contaminated is 689 m3 (equivalent to 1,381 tons). Meanwhile, when using a combination of geoelectric data and grid sampling on the suspected area, the indicated volume of contamination was 594 m3 (equivalent to 1,190 tons). These results can be concluded that using a combination of geoelectric methods and grid sampling in identifying the presence of contamination on the soil surface can explain quantitatively and qualitatively the volume of contaminated soil with an accuracy of 115%.